2007
DOI: 10.1093/acprof:oso/9780199213603.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Ions and electrons in liquid helium

Abstract: In liquid helium, an electron is surrounded by a cavity called an electron bubble of 20 Ångstroms in diameter. A positive helium ion is solvated by an electrostriction induced solid helium-ice shell called a snowball of 7 Ångstroms in diameter. By studying their transport properties, these objects are well suited for the testing of the microscopic properties of superfluidity. At low temperatures and with small electric fields, the drift velocity of the charges depends on their interaction with the elementary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
83
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(87 citation statements)
references
References 681 publications
3
83
0
1
Order By: Relevance
“…Electrically charged particles have been one of the most effective probes to study properties of 4 He in the superfluid state. Beginning with the pioneering works of Williams [1], Careri et al [2], and Reif and Mayer [3], it has been observed that ions moving through liquid helium due to an external applied electric field can interact with different types of excitations that act to produce a drag force on the ion [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrically charged particles have been one of the most effective probes to study properties of 4 He in the superfluid state. Beginning with the pioneering works of Williams [1], Careri et al [2], and Reif and Mayer [3], it has been observed that ions moving through liquid helium due to an external applied electric field can interact with different types of excitations that act to produce a drag force on the ion [4].…”
Section: Introductionmentioning
confidence: 99%
“…By using the GrossClark model, in which a Gross-Pitaevskii equation for the superfluid wave function is coupled to a Schrödinger equation for the electron wave function, we study how vortex nucleation affects the measured drift velocity of the ion. We use parameters that give realistic values of the ratio of the radius of the bubble with respect to the healing length in superfluid 4 He at a pressure of one bar. By performing fully three-dimensional spatiotemporal simulations of the superfluid coupled to an electron, that is modeled within an adiabatic approximation and moving under the influence of an applied electric field, we are able to recover the key dynamics of the ion-vortex interactions that arise and the subsequent ion-vortex complexes that can form.…”
mentioning
confidence: 99%
“…Atkins' snowball model for K + predicts an effective ion mass 45× the mass of a helium atom and a radius of 6Å. 9 Ion mobility in superfluid helium is essentially determined by the following aspects: 10 (i) the number of helium atoms dragged with the ion, (ii) dissipation of energy through emission of sound when the ion is accelerated in the liquid, (iii) roton emission when the Landau critical velocity is exceeded, (iv) vortex nucleation when the corresponding critical velocity is exceeded, and (v) interaction with thermal excitations when T > 0 K. The first effect is independent of the bubble radius (R b ) and does not depend strongly on temperature provided that the rigidly bound solvent atoms remain attached to the ion. The second effect depends on R b through ion acceleration (phonon emission), and for an inviscid liquid it is given by 1 2 Vρ 0 , where V is the bubble volume and ρ 0 is the bulk liquid density.…”
Section: Introductionmentioning
confidence: 99%
“…There, like in the normal liquid phase, the motion is governed by the laws of hydrodynamical (Stokes) flow, whereas in the superfluid state interactions with collective excitations (phonons, rotons and vortices) become dominant. 11 In all of these flow regimes the radius of the spherical cavities determines the mobility. In the gas phase at lower densities, cavities are not supported.…”
Section: Introductionmentioning
confidence: 99%